Effects of High Carbon Dioxide Concentration on Stored-Product Insects, Aflatoxin Production and Storage Quality Changes in Cocoa Beans - Wahyudi, Teguh (2003)
The potency of C0₂ gas as an alternative fumigant in controlling stored-product insects, its inhibitory characteristics on the growth of molds and mycotoxins production and quality changes of the treated cocoa beans have been evaluated in four consecutive research experiments. These experiments were focused on the use of high CO₂ concentration during fumigation and followed by prolonged storage practices in laboratory hermetic room, under plastic enclosures or high-pressure chamber. As comparison, treatments using methyl bromide, phosphine and normal air atmosphere were also carried out. Carbon dioxide concentration of 40, 60 and 80% were effective in controlling Ephestia cautella and Araecerus Jasciculatus during 1 to 3 months of exposure, whereas the test insects in the control showed 20-27 survivors for E. cautella and 20 surVIvors for A. Jasciculatus from the initial number of 30 and 20 insects, respectively. This study also found no significant effect of high CO₂ concentration treatments on cocoa beans quality during the exposure time. The growth of A. flavus and aflatoxins production (except for aflatoxin B2) was significantly inhibited in the presence of high concentration of CO₂ atmosphere during I-month storage. Free fatty acids production in the treated cocoa beans was not inhibited by the treatments. Methyl bromide concentration of 15 g/t or 0.66 g/t of phosphine were required to control E. cautella, A. Jasciculatus and Tribolium castaneum. Levels of methyl bromide residues increased from 0.27 ppm to 1.27, 1.49 and 3.10 ppm with an increase in concentration of methyl bromide from 3 g/t to 5,10 and 15 g/t, respectively. Phosphine residues increased from 0.07 ppm to 0.12, 0.11, 0.14 and 0.15 ppm with an increase in concentration of phosphine from 0.33 g/t to 0.66, 1, 2 and 3 g/t respectively. Methyl bromide fumigation resulted in methylation of proteins as indicated by the formation of 7 -methyl guanine in treated cocoa beans. Complete elimination of E. cautella was achieved by using C02 under high-pressure at 4 bar within 4 hours of exposure. A longer exposure time of 6 hours was needed to control A. Jasciculatus and T. castaneum at the same pressure. Complete elimination was also achieved at 7 bar within 4 hours of exposure or at 10 bar within 2 hours of exposure for controlling A. fasciculatus and T. castaneum. In the control treatments using normal air at 10 bar within 4 hours of exposure, the percent RIE (reduction in emergence) for E. cautella was only 3.33% whereas no mortality were found for T. castaneum and A. fasciculatus. Carbon dioxide under high-pressure treatments exhibited low possibility to effect the quality of the treated cocoa beans.